2021
DOI: 10.1109/ojcoms.2021.3113023
|View full text |Cite
|
Sign up to set email alerts
|

Wireless-Powered Full-Duplex UAV Relay Networks Over FTR Channels

Abstract: A thorough understanding of fundamental limits of wireless-powered unmanned aerial vehicle (UAV) relay networks in millimeter waves is still missing. We narrow this gap by investigating the outage performance of a UAV-assisted wireless network over fluctuating two-ray (FTR) channels. The FTR fading model is particularly appealing since well characterizes the wireless propagation in a wide range of frequencies, including those in millimeter waves. The proposed setup consists of a source-destination pair communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…UAV-assisted SWIPT, as an upsurge of recent research topic, has gained momentum rapidly. The existing UAV-enabled SWIPT literature can be broadly divided into three categories, which are cooperative SWIPT networks [217]- [229], multicasting SWIPT networks [230]- [247] and millimeter-wave (mmWave) SWIPT networks [199], [248]- [253]. Apart from these, there are a few works in the literature that facilitate disaster aware clustering and association [254], and secure information and power transmission [255].…”
Section: Uav-enabled Swipt Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…UAV-assisted SWIPT, as an upsurge of recent research topic, has gained momentum rapidly. The existing UAV-enabled SWIPT literature can be broadly divided into three categories, which are cooperative SWIPT networks [217]- [229], multicasting SWIPT networks [230]- [247] and millimeter-wave (mmWave) SWIPT networks [199], [248]- [253]. Apart from these, there are a few works in the literature that facilitate disaster aware clustering and association [254], and secure information and power transmission [255].…”
Section: Uav-enabled Swipt Systemsmentioning
confidence: 99%
“…Millimeter-wave bands give key enablers for the revolutionary facilities with the wide swaths of unused and unexplored spectrum. Towards this, the available literature has presented a few mmWave UAV-enabled SWIPT studies that can be basically grouped as single-user [250], [253] and multiuser communication [199], [251], [252]. These studies are summed up in Table VI.…”
Section: Uav-enabled Mmwave Swipt Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, it is considered that the UAV relay position remains unchanged (or that the UAV speed is sufficiently low) during a certain time interval in order to serve the ground users. Nevertheless, power-limited constraint, which affects the flight time can be taken into account for future studies, and there are some related works that can be found in [59], [60]. Throughout this paper, we assume that problem (26) is always feasible when the QoS requirement of each user will be satisfied if a ij = 1.…”
Section: Problem Formulationmentioning
confidence: 99%